Alternative explanation of some total so-lar eclipse related phenomena - Abunayib, Salah (International Journal of Advanced Astronomy, 2017)
Diamond ring, shadow bands and coronal heating are some phenomena of great interest to concerned scientists and observers during total eclipse of the sun. These phenomena are explained here in a different way which is simply based on the familiar fact that the sun and the moon are actually spherical objects and not just plane disks. Firstly, the diamond of the diamond ring is seen here as two symmetrical seamless joined halves. One-half is the directly seen single spot of the sun that is uncovered by the moon just at the beginning and end of totality. The other half is a mirror image of that spot reflected by the edge surface of the moon. Secondly, the shadow bands phenomenon is explained as due to interference of light from two seamless joined hair crescents. One is the inner edge of the thin crescent sun that can be seen immediately before and after totality. Light from this inner edge hair crescent falling on the edge surface of the moon gets mirror reflected creating another hair crescent image and both are seamlessly embraced by the main crescent sun. Thirdly, during totality when looking at the outer atmosphere of the sun around its eclipsed face, one is actually looking through a very deep transparent atmosphere of the sun. The viewed depth in the outer atmosphere is geometrically hundreds of times greater than that of the photosphere at the center of the face of the sun. Theoretically, the solar energy gets concentrated by the integral effect of all the points along the viewed depth. This may, hence, stand as one of the factors to be considered in explaining the peculiar phenomenon that the temperature increases as we go away from the surface of the sun.